High stable polarization-insensitive Er-doped Q-switched fiber laser with iron oxide nanoparticles as saturable absorber. (May 2019) - Pang, Lihui; Song, Chenghua; Lv, Ruidong; Chen, Zhendong; Liu, Sicong; Wu, Rongqian; Lv, Yi; Liu, Wenjun
Highlights: The iron oxide nanoparticles is synthesized via chemical co-precipitation method. The self-Q-switched operation can be presented with the absence of polarizer controller. The shortest pulse duration is 896 ns. Abstract: All fiber Q-switched laser with its advantages of high energy, compact structure and high stability boosted the growing demand in many applications. We synthesized the regular iron oxide nanoparticles (IONP) in size of 12–15 nm via the chemical co-precipitation method. Using the IONP-PVA film as SA, high stable polarization-insensitive Er-doped Q-switched fiber laser was demonstrated. The prepared IONP SA exhibits saturation intensity of 13.44 MW/cm 2 . The shortest pulse duration was achieved to be 896 ns and the single pulse energy was up to 100 nJ with the maximum pump power of 500 mW. In particular, the polarization controller is unnecessary in our experiments, so the ring cavity can be compacted into a smaller size with 80 dB signal-to-noise ratio for the output pulse sequence. Such a compact, low cost and high stability Q-switched laser maybe expected to have the more extensive application prospect.